PENGARUH DIMENSI FRAUD TRIANGLE (TEKANAN, KESEMPATAN DAN RASIONALISASI) TERHADAP PERILAKU KECURANGAN AKADEMIK PADA MAHASISWA - Dewi Surtika Sari, Rispantyo & Djoko Kristianto (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2017)
The purpose of this study was to analyze: 1) the significance of pressure effecton the behavior of fraud academic on the students, 2) the significance of opportunityeffect on the behaviour of academic fraud on the students 3) the significance ofrationalization effect on the behavior of academic fraud on the students. The type ofthis study is a survey of students of Faculty of Economics Accounting Study ProgramSlamet Riyadi University Surakarta class of 2013 and 2014. The sample techniqueused convenience sampling with sample of 57 students. Methods of data collectionused documentation and questionnaires. Data analysis techniques used multiplelinear regression. The results showed that the pressure had a positive and significanteffect on student’s academic fraud behavior. Opportunities had a positive andsignificant effect on student’s academic fraud behavior. Rationalization has apositive and significant effect on student’s academic fraud behavior.Keywords: fraud triangle, pressure, opportunity, rationalization, fraud academic